TO THE HISTORY OF BREEDING FOR LATE BLIGHT RESISTANCE IN POTATO UP TO 1960IES – A REVIEW - Darsow, Ulrich (Potato Journal, 2017)
ABSTRACT: The dramatic appearance of late blight in Europe in 1845 and the following years gave a push for developing of plant pathology and potato breeding. Variety Champion was a milestone in the early history of breeding for quantitative blight resistance, determined by polygenes. Private breeders selected lowest blighted clones in field conditions from gene pool of cultural potato. The insufficient results then achieved are underestimated today.Detection of simple inherited late blight resistance as qualitative trait in wild potato material followed intensive phytopathological and breeding work in public financed institutes. Expeditions to South and Middle America resulted in establishing of gene banks for potato species, increased knowledge of it including their blight resistance and other traits and its use in breeding. Interspecific hybrids included mainly S. demissum as source of resistance and were used to breed varieties with R-genes released after 1930. Examples of parentages are given. Occurrence of races of P. infestans could be identified since 1932 by differentials possessing different dominant R-genes. Now one could distinguish between qualitative (R-gene coded hypersensitivity) and quantitative resistance. Laboratory methods of assessment of resistance were developed mainly on foliage, but also on tubers and were applied in large scale. Quicker development of new virulent races than breeding could counteract with new resistant cultivars finished use of race-depended type of resistance after 1960ies. Application of oomycides became the main measure of protection.